The Effect of Education and Supplementary Food Based on Local Food on the Level of Knowledge, Energy and Protein Sufficiency Levels, and Improvemenin Nutritional Status Among Children with Malnutrition at the Bairo Pite Clinic, Lanud-Dili, East Timor - Yustina Kore Fouk; Ali Rosidi; Ari Istiany (Eduvest - Journal of Universal Studies, 2026)
This research aims to formulate competitive strategies for Permata Hotel Bogor as a local business hotel in response to increasing competition and ongoing digital transformation in the hospitality industry. The research adopts a mixed-method approach with a sequential exploratory design, combining qualitative insights, customer perceptions derived from online reviews, and quantitative strategic analysis. Data were collected through in-depth interviews, Focus Group Discussions (FGDs), observations, and documentation. In addition, customer reviews were analyzed using R Studio through text mining and sentiment analysis to identify key issues, sentiment intensity, and their impact on customer satisfaction. The identified factors were then evaluated using Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices, followed by a SWOT analysis, and prioritized using the Quantitative Strategic Planning Matrix (QSPM). The findings indicate that strengthening digital marketing and optimizing Online Travel Agent (OTA) channels represent the highest-priority strategy (TAS = 3.07), followed by market diversification (TAS = 2.87) and facility modernization (TAS = 2.68). Overall, this study highlights the importance of adopting a data-driven strategic approach to enhance competitiveness and sustainability in the hospitality industry.